An Analysis Of The Determination Of The Cost Of Production Based On Order At Yanto Mie Milling Business In Muara Bangkahulu Of Bengkulu City - Elisabeth Sekar Ambar Pratiwi; Neri Susanti; Abdu Rahman (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
This study aims to find out the calculation of the cost of production based on orders placed by the Yanto Mie Milling Business and using job order costing in August 2022. The cost of production is a cost incurred to process or produce raw materials into goods ready for sale. In this study using the job order costing method where the cost of all production costs is collected for a particular product which can be separated from the identity of each product and the cost price is determined individually or the collection of production costs to determine production prices in businesses that produce products on an order basis. Yanto Mie Milling Business is engaged in culinary business or food sources. This business has been established since 2014 until now, which is located at Grand Kopri Housing Block A No. 88, Muara Bangkahulu, Bengkulu City. The analytical method in this study uses quantitative research. The results of the study show that there is a difference in the calculation of the cost of production carried out by the Yanto Mie Milling Business and that carried out by the author using job order costing. The calculation of the cost of goods carried out by the Yanto Mie Milling Business is Rp. 14,077,000, while the author uses job order costing of Rp. 14,867,000. The difference between the two calculations is Rp. 790,000. Because the Yanto Mie Milling Business still has a lot of costs that are not charged in the calculation of the cost of production, such as overhead costs that are not charged and non-production costs that are not charged. There is a difference in determining the selling price in this study, the difference is Rp. 1,518. The difference in the selling price was caused because the Yanto Mie Milling Business was not based on a percentage. That way the difference in profit/kg between the two calculations is IDR 1,365.